2021
DOI: 10.1016/j.annonc.2021.08.2096
|View full text |Cite
|
Sign up to set email alerts
|

LBA22 Neoadjuvant chemotherapy with oxaliplatin and capecitabine versus chemoradiation with capecitabine for locally advanced rectal cancer with uninvolved mesorectal fascia (CONVERT): Initial results of a multicenter randomised, open-label, phase III trial

Abstract: Background: Combined chemoradiation therapy is currently the standard practice for locally advanced rectal cancer (LARC) with uninvolved mesorectal fascia (MRF). The CONVERT study compares neoadjuvant chemotherapy with CapeOx alone to standard chemoradiotherapy (CRT) with Capecitabine for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Generally, the pCR rate of patients with LARC who receive nCT is <10% 23 . Despite the CONVERT trial's suggestion that nCT alone can achieve an 11% pCR rate, patients enrolled in the nCT arm had a low burden 24 . Another phase II trial treated patients with mFOLFOXIRI for five cycles as a neoadjuvant regimen 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the pCR rate of patients with LARC who receive nCT is <10% 23 . Despite the CONVERT trial's suggestion that nCT alone can achieve an 11% pCR rate, patients enrolled in the nCT arm had a low burden 24 . Another phase II trial treated patients with mFOLFOXIRI for five cycles as a neoadjuvant regimen 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Only limited data from the randomized phase II study, FOWARC, 10 suggested it may lead to similar outcomes as chemoradiation. In the CONVERT study, presented by Pei-Rong Ding et al., 11 663 patients with locally advanced rectal cancer with uninvolved mesorectal fascia-negative were randomized to four neoadjuvant cycles of CapeOx (nCT) or chemoradiation with concurrent capecitabine (nCRT). The early outcomes for both arms were similar, although nCRT was superior in the degree of tumour regression calculated as TRG 0-1 (38.6% for nCRT versus 24.0% for nCT; P < 0.001) with similar pathological complete responses rates (13.8% for nCRT and 11.0% for nCT; not significant).…”
Section: Lower Gastrointestinal Tractmentioning
confidence: 99%
“…In the FOWARC study, though the neoadjuvant with mFOLFOX6 alone achieved a postoperative pCR rate of 6.6%, the rates of R0 resection (89.4% vs 90.7%), anal preservation (89.5% vs 84.4%), and 3-year local recurrence (8.3% vs 8.0%) were similar compared to CRT, as well as producing less postoperative complications [ 10 ]. The 2021 ESMO congress CONVERT trial enrolled patients without mesorectal fascia (MRF) invasion based on pelvic magnetic resonance images (MRI) at baseline [ 11 ]. Four cycles of XELOX regimen chemotherapy showed comparable pCR (11% vs 13.8%) and downstaging rates (40.8% vs 45.6%), with capecitabine-based CRT in a neoadjuvant setting.…”
Section: Introductionmentioning
confidence: 99%